Reading Habits among Post Graduate students of GMD Arts, BW Commerce & Science College Sinnar District-Nashik (MS): Investigating reading habits among post graduate students (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Reading could be a way to get a higher knowledge of one’s own experiences and it can be an exciting journey to self-discovery. Reading transfers experiences to the individual, so that the reader may expand one’s horizons, identify, extend and intensify his or her interest and gain a deeper understanding of the world. A good reading habit is important for healthy intellectual growth and plays a really crucial role in enabling an individual to attain sensible efficiency. Reading habit is an active skill-based method of constructing that means and gaining information from oral, visual and written communication. The present study was conducted on 224 P.G. students from GMD Arts, BW Commerce Science College Sinnar Dist. Nashik of Maharashtra State. The basic aim of the study is to investigate the reading habit of the P.G. students particularly based on reading materials, time spent for reading, and impact of the internetsocial media on their reading habits. The study is based on the survey method and 224 questionnaires distributed to P.G. students and received feedback and analyzed. The result reveals that there was a significant difference in reading habits in relation to the time spent for reading, use different reading materials, the impact of the internetsocial networking tools on reading habits, and search of study material on mobile internet by P.G. students. Preference of reading materials clearly shows that the majority of P.G. students read subject books, followed by a motivational book, newspapers, storybooks, novels, biographical books, magazinesjournals, poems and travel guidebooks etc.